Production and periodicity in the emergence of cercariae of Diplostomum spp. (Digenea) from snails Radix lagotis (Lymnaeidae) - Vyhlídalová, Tereza (Jihočeská univerzita, 2020)
The cercarial emergence patterns of three species of Diplostomum (D. mergi, D. spathaceum and D. pariventosum) parasitising freshwater first intermediate host Radix lagotis were studied under various experimental conditions, i.e., field, laboratory and incubator, and seasons, i.e., spring, summer and autumn. This study provided novel data on the production and periodicity in cercarial emergence and revealed both interspecific and intraspecific variaons related to the species-specific adaptive nature of cercariae to facilitate transmission to second intermediate fish hosts.
Production and periodicity in the emergence of cercariae of Diplostomum spp. (Digenea) from snails Radix lagotis (Lymnaeidae)
Keywords: Cercariae; Trematoda; Emergence; Prevalence; Diplostomum spathaceum; Diplostomum mergi; Diplostomum parviventosum; Radix lagotis; Freshwater fish; Freshwater; Transmisson.; Cercariae; Trematoda; Emergence; Prevalence; Diplostomum spathaceum; Diplostomum mergi; Diplostomum parviventosum; Radix lagotis; Freshwater fish; Freshwater; Transmisson.